Makānatu Al-ḥāsūb Al-ālῑ Fῑ Ta’lῑmi-al-lugah Al-‘arabiyyah - Fairuz Subakir Ahmad; A.Y. Linda Eka Santi (University of Darussalam Gontor, 2018)
Abstract That educational aids help the teacher in the face of large numbers of students and the density of classrooms after the education became mandatory in some stages and increased awareness and education has a great place in the hearts of people. It also draws students to the lesson and draws attention to it and make the impact of what they learn to stay and continue and help them to quickly remember the information related to a tangible sensory basis. And educational technology methodology in thinking focuses on the theoretical and practical aspects of the teaching and learning procedures and resources design, implementation, development and management, to upgrade the educational process, and access to perfection. It is an integrated composite process that includes human resources, material resources, ideas and actions that lead to solutions to educational problems that hinder the progress and development of human learning. The computer may still dazzle us every moment with its multiple abilities to penetrate our lives, and in most countries of the world and through the educational institutions in which the reliance on the computer in education is an essential element of the educational process. The study reached several results, most notably that the field of teaching and learning the Arabic language benefited greatly from the potential of the computer. And that the creativity of the teacher has an effective role in the benefit of the use of the computer, as the use of education in several ways, it is several methods of teaching group in one, and the study resulted in several problems are human and financial resources, Between language teachers, programmers, the lack of technological awareness, the negative attitudes of some teachers, and the lack of widespread self-learning. ملخصأن الوسائل التعليمية تساعد المدرس في مواجهة أعداد الطلبة الكبيرة وكثافة الفصول الدراسية بعد أن أصبح التعليم ألزاميا في بعض مراحله وازداد الوعي واحتل التعليم مكانة كبيرة في نفوس الناس. كما أنها تشوق الطلبة للدرس وتوجه اهتمامهم إليه وتجعل أثر ما يتعلمونه باقيا ومستمرا وتساعدهم على سرعة تذكر المعلومات لارتباطها بأساس حسي ملموس. وتكنولوجيا التعليم منهجية في التفكير تركز على الجوانب النظرية والعملية لإجراءات التعليم والتعلم ومصادره تصميما وتنفيذا وتطويرا وإدارة، وذلك لترقية العملية التعليمية، والوصول إلى درجة الإتقان. وهو عملية مركب متكاملة تتضمن الموارد البشرية والموارد المادية والأفكار ولإجراءت التي تؤدي إلى إيجاد الحلول للمشكلات التربوية التي تعوق تقدم وتطور التعلم الإنساني. وقد يظل الحاسوب الآلي يبهرنا كل لحظة بقدراته المتعددة على التغلغل في شؤون حياتنا، وفي أغلب دول العالم وعبر المؤسسات التعليمية الكائنة بها أصبح الاعتماد على الحاسب الآلي في التعليم يشكل عنصرا أساسيا من عناصر العملية التعليمية. فتوصلت الدراسة لعدة نتائج من أبرزها أن مجال تعليم وتعلم اللغة العربية استفاد كثيرا من إمكانات الحاسوب الآلي. وأن إبداع المعلم له دور فاعل في تحقيق الفائدة من استخدام الحاسوب الآلي، حيث إن الإفادة منه في مجال التعليم لها طرق متعددة، فهو يعد عدة وسائل تعليمية مجموعة في واحد، كما أسفرت الدراسة عن وجود عدة مشكلات تتمثل في الموارد البشرية والمالية، وعدم تحقيق التكامل بين أساتذة اللغة، والمبرمجين، و غياب الوعي التكنولوجي، والاتجاهات السلبية لدى بعض المعلمين، وعدم شيوع عملية التعلم الذاتي.الكلمة الرئيسية: الوسائل التعليمية، تكنولوجيا التعليم، الحاسوب الآلي